Pregnancy in the obese woman: special considerations - Pacheco-Romero, José (2017)
Obesity would be the most common health problem for women of reproductive age. Pregnancies complicated with obesity are associated with gestational diabetes, preeclampsia, preterm birth, instrumental delivery and cesarean section, infections and postpartum hemorrhage. And the baby is at higher risk of congenital malformations, macrosomia, shoulder dystocia, and fetal death. The implications related to the management of obesity in pregnancy are not well understood due to lack of evidence-based management options. The management of obesity should start before the woman gets pregnant, following the rule that a woman should be in the best physical and mental conditions if she wants to have a baby. The health provider in charge of the prenatal care needs the support of a dietitian or an endocrinologist. Obese women are more likely to have difficulties during labor and delivery and require both special infrastructure and care by specialized physicians. Future health problems of mother and baby are considered in this review.